The Presence of Migratory Shorebirds on the Coast of Aceh Besar Beach and Banda Aceh - Khairunisak; Aida Fithri; Firdus; Heri Tarmizi (Jurnal Penelitian Pendidikan IPA, 2025)
The coast of Aceh Besar and Banda Aceh is one of the areas that is a stopover site for migratory shorebirds. This study aims to identify the types of migratory shorebirds and habitat types that support the presence of migratory shorebirds on the coast of Aceh Besar and Banda Aceh. The research was conducted in February to April 2024. The method used in this study is Purposive sampling with Point count. Data collection of migratory shorebirds species is carried out using point count. The study results show that 1.244 individuals migratory shorebird visit on the coast of Aceh Besar, that is Numenius phaeopus, Numenius arquata, Pluvialis fulva, Charadrius mongolus, Charadrius leschenaultii, Gallinago megala, Calidris minuta, Actitis hypoleucos, Xenus cinereus, and Limosa lapponica. Type of habitat used by migratory shorebird are mangroves, ponds, beaches, muddy plains, and grassy fields. On the coast of Banda Aceh 433 individuals migratory shorebird with habitat types of mangroves, ponds, muddy plains and beaches, that is Numenius arquata, Pluvialis fulva, Charadrius mongolus, Charadrius leschenaultii, Actitis hypoleucos. The diversity of migratory shorebirds on the coasts of Aceh Besar and Banda Aceh is in the medium category. It is necessary to establish protection areas for migratory shorebird and educate the public about the importance of preserving the enviroment.